KORELASI RESPON SISWA TERHADAP PENGGUNAAN MEDIA PEMBELAJARAN AUDIO VISUAL DENGAN PRESTASI BELAJAR MATA PELAJARAN MATEMATIKA POKOK BAHASAN LUAS TABUNG DI KELAS IX SMP ISLAM SURABAYA - Handono, Handono; Taufiq, Mohammad (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2016)
Mathematic is discipline that has a vital role in an effort to master of science and technology. Since the importance of mathematics, the mathematics learning process for students needs special attention. Therefore, teachers should also be able to select appropriate learning methods. One of the methods that is appropriate to help students learning math is to use Audio Visual learning media, because the media is very interesting since there are animation, images, audio, visuals involved in it. It can help students to visualize mathematical concepts in realistic. Based on the above, the authors choose the title in this study as follows: Correlation Response Students Against Use of Instructional Media Audio Visual With Subjects Mathematics Learning Achievement Highlights Size Tube In Class IX SMP Islam Surabaya. In this study the authors used quantitative research methods using the non-parametric Spearman Rank correlation data analysis for hypothesis testing. The population of this research was all Surabaya Islamic junior high school students, while samples of this study were all students of class IX SMP Islam Surabaya totaling 40 students. The result of analysis of this study was the percentage which obtained from the questionnaire responses of the students was increased.It means that the value of student achievement increasing also.It can be concluded that there was a correlation between students' response to the use of instructional media Audio Visual (X) with the learning achievement (Y) students class IX SMP Islam Surabaya and of the results were positive and the statistical correlation value is greater than 5% ie 0.968 it can be said that there is a significant correlation.